Promoting Teachers’ Well-being through Positive School Leadership Practices : Perspectives of Islamic Religious Education Teachers in Indonesia - Nur Diyanto, Yuli (My University, 2024)
Teachers’ well-being is important for Islamic Religious Education teachers in Indonesia. Thus, they can carry out their roles well in developing students’ noble character, which is an essential goal of the Indonesian education system. This research aims to promote the well-being of Islamic Religious Education teachers in Indonesia through positive school leadership practices. A qualitative approach is employed in this research and data was collected using semi-structured interviews. The participants consist of 14 Islamic Religious Education teachers in Indonesia who have different backgrounds. The results of this research reveal six important aspects that can be considered by school leadership to improve teachers’ well-being: building positive relationships, promoting positive emotion, facilitating engagement, creating meaningfulness, supporting accomplishment, and maintaining spirituality. Positive relationships are an essential element in teacher well-being. Principals who take various steps to build positive relationships at school contribute to fostering a supportive work environment which is crucial to teachers’ well-being. Moreover, teachers perceived increased motivation and engagement from the principal’s leadership practices that created positive emotions. For Islamic Religious Education teachers, aspects of spirituality and meaningfulness have a pivotal role in resilience and work purpose, thus school principals need to maintain these aspects. Furthermore, appreciation from school principals, support for professional development, and adequate financial compensation were identified as important in maintaining the commitment of teachers. These factors together will create a positive school environment that enables teachers to flourish and benefit the students. This research provides valuable insights for school leaders and policymakers to promote the well-being of Islamic Religious Education teachers in Indonesia therefore they can perform their roles effectively.
Keywords: Teacher well-being, Islamic Religious Education teachers, School leadership